Neuronal Plasticity Associated with Burn Injury and Its Relevance for Perception and Management of Pain in Burn Patients - Terence J Coderre; Manon Choinière (Pain Research and Management)
Through the introduction of the gate control theory and various subsequent works, Ronald Melzack has inspired many investigators worldwide to realize two important facts about pain. First, incoming pain messages are subject to both negative and positive modulation, which significantly affect its perception. Second, the progression of knowledge about the basic mechanisms underlying persistent and chronic pain is critically dependent on the increased understanding of the complexity of the symptoms experienced by pain patients. The present paper examines these two very important issues in an effort to understand better the mechanisms that underlie the pain suffered by burn patients. The physiological responses to burn injury involve many different mediators and mechanisms, all of which contribute to pain perception and development of neuronal plasticity underlying short and long term changes in pain sensitivity. While experimental burn injuries in humans and animals are typically well controlled and mild, in burn victims, the severity is much more variable, and clinical care involves repeated traumas and manipulations of the injured sites. Recurrent inputs from damaged and redamaged tissue impinge on a nervous system that becomes an active participant in the initiation of changes in sensory perception and maintenance of long term sensory disturbances. Recently acquired experimental evidence on postburn hyperalgesia, central hyperexcitability and changes in opioid sensitivity provides strong support that burn patients need an analgesic approach aimed at preventing or reducing the 'neural' memory of pain, including the use of more than one treatment modality. Burn injuries offer a unique opportunity to combine experimental and clinical research to understand pain mechanisms better. Over the years, Ronald Melzack has insisted that one of the most laudable enterprises in research is to span the gap between these two often separate worlds.